DISABILITY RIGHTS AND EMERGING DISABILITY LEGISLATION IN SELECTED AFRICAN JURISDICTIONS: A DIAGNOSTIC COMMENTARY (African Disability Rights Yearbook, 2021)
The Convention on the Rights of Persons with Disabilities (CRPD)1 expects states parties to take appropriate legislative, administrative and other measures for implementing disability rights.2 These measures are expected to incorporate the standards set by the CRPD. A number of Africa states parties to the CRPD have disability specific legislation for implementing disability rights. These countries include Malawi,3 Zambia,4 Uganda,5 Kenya,6 United Republic of Tanzania (Tanzania),7 Ghana,8 and Zimbabwe.9 This commentary analyses the extent of compliance with the CRPD’s standards by the disability legislation adopted in selected African jurisdictions. The assessment is done by analysing conformity to four thematic aspects, namely: the human rights based understanding of disability; equality and non-discrimination; existence of a national disability body for coordinating the implementation of disability rights; and the provision for redress mechanism for violation of disability rights. The commentary also looks into whether the disability legislation contains substantive rights, especially education, employment, healthcare, accessibility, equal legal capacity and social protection. These four aspects and the question of guarantees for substantive rights have been selected since many people with disabilities often suffer human rights violations with regard to these contexts.10